Penerapan Metode Pelibatan Pasien melalui Feedback Pasien Dan Edukasi Speak-Up Di Ruang Rawat Inap Rumah Sakit X Jakarta: Pilot Study - Fauziyah, Nuridha; Hariyati, Rr Tutik Sri; Fatmawati, Umi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
One of patient-centered-cared domaind can be done by listen to the patients voices about the servicesprovided and motivate patients to actively involved in the treatment process. Patient involvement methods:patient feedback and Speak-up education are methods that can be applied in hospitals. This study aims toimplement the development of patient imvolvement methods:patient feedback and Speak-up education. Themethod used was a pilot study of 57 nurses using observation sheets of the patient feedback process andSpeak-up consisting of 17 items. The study begin with problem identification, fishbone analysis,implementation and evaluation. Implementation consisted of making guides, SPO, forms, and role-playvideos. The results of the study showed that the patient feedback method and Speak-up were performed withan achievement of 69.42%. Conclusion: the success of the patient involvement process was influenced bythe willingness of the organization and staff to listen to the patients voice, readiness to change, supportiveresources, and support of nurses, nurse managers and management. Recommendation: this study is thebasis for the application of new methods of involving patients in the hospital